Istikhdam kitab al-I’rab li al-Habib Hasan bin Ahmad Baharun Litarqiyat maharat al-Qira’ah : Dirasah Midaniyah fi ma’had al-Raudhah Surabaya - Moh Syaifudin; Abdullah, Abdullah (Qismul Arab: Journal of Arabic Education, 2023)
This study aims to determine the effect of using the I'rob book by AL-Habib Hasan bin Ahmad Baharun at the AR-Roudloh Islamic boarding school in Surabaya to improve reading skills. This study uses a quantitative approach. The subjects of this study were 15 students from the AR-Roudloh Islamic boarding school in Surabaya. The data analysis technique used is the t-test with the help of SPSS software. The results of this study indicate that there is a significant difference between before and after the application of using the AL I'rob book, this is proven through the t-test by obtaining a statistical price of t = 5,405 with df = 14 and a significant number or p-value = 0.000 < 0.05 or Ho is rejected and Ha is accepted. This shows that the use of the book AL I'rob by AL-Habib Hasan bin Ahmad Baharun at the AR-Roudloh Islamic boarding school in Surabaya is effective in improving students' reading skills